Food loss in international trade: A case study of Indonesian tuna exported to the European Union, the United States, and Japan - Sahara Sahara; Syarifah Amaliah; Dian Verawati Panjaitan; Mutiara Probokawuryan (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2022)
The knowledge of the drivers of food losses in international trade and possible mitigation strategies is still limited. This study focused on the prevalence and drivers of food loss in Indonesian tuna exported to the European Union, the United States, and Japan. The results showed that various existing Non-Tariff Measures (NTMs) are in place to ensure food safety. However, standards and regulations differ significantly among trade partners, and are somewhat more strict than international standards, leading to higher rejection levels. Food loss is evident in the cross-border tuna trade as 20 to 30 per cent of Indonesian tuna is rejected annually. Drivers of food loss are classified as micro-level drivers consisting of post-harvest damages, lack of infrastructure and facilities; improper sanitation and hygiene in the processing unit, inability to fulfil food safety standards, and socialization of the standards and regulation. Macro-level drivers are related to the increasing use of NTMs, varying and relatively stricter food safety standards, transparency issues, trading procedures, and institutional factors. At the micro-level, it is important to improve tuna export quality infrastructure and boost the capacity of actors in the value chains to implement best practices. Increasing the socialization about the food safety standard and import regulations and international standards (particularly Codex Alimentarius) is also needed. Meanwhile, NTM streamlining and improving transparency with national trade portals and help desk services are also important to facilitate trade and reduce food loss.
Keywords: F14; Q22; 330; Food loss; Import rejection; Non-Tariff Measures (NTMs); Tuna